ADAKAH ITU: VERITAS ET IUSTITIA? - Kusumohamidjojo, Budiono (Faculty of Law, Parahyangan Chatolic University, 2015)
AbstractThe idea of truth has gone through a path of a long history and will still be the subject of a long and complex discourse. It will even remain being the cause of violent conflicts, the more if it deals with the perception of absolute truth. The unfortunate problem befalling mankind is the fact, which is based on different perceptions of truth, let alone âabsolute truthâ, that a lot of people strive to uphold perfect justice as if the world has a place for such an illusion. The history of mankind has reached a stage, whereby we must learn to understand that we have to distance ourselves from thoughts of promoting absolute truth, the more if aspirations toward upholding perfect justice also piggy backs thereon. Or else the world will keep constantly embroiled in senseless conflicts, violence and wars, where people would fight each other for their respective absolute principles, while actually being unaware about its absurd logic. Therefore the newly launched journal Veritas Et Iustitia would have to confront a tremendous challenge because the editors should construct a platform for continuous dialogue leading to constructive efforts towards better understanding about truth which should be increasingly more true and justice which should be increasingly more just to be pursued by mankind.Â Keywords: truth, justice, history, absolutism, ideology, paradoxically